(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The oral tradition remains a unique testament to the capacity of the human brain to absorb, remember and reproduce structures of great complexity and sophistication without a system of written notation. As the research article is related, the researcher has written an oral tradition in the sphere of music. The teaching of classical music has primarily been oral. The raga and its structure, the intricate nuances of tala or rhythm, and the rendering of raga and tala as bandish or composition, are passed on from guru to shishya by word of mouth and through direct demonstration. There is no printed sheet of music, with notation acting as the medium, to impart knowledge. With the passage of time many institutes introduced music education, it also been part of syllabus. The article is all about the oral tradition in music sphere.